Viroconium
This was the site of a regional (cantonal) capital, of which Roman Britain had fourteen. It was important as a road junction and river crossing, and is mentioned in Ptolemy's Geography of the Second Century C.E. As with many of the Roman sites, it was abandoned with the breakup of the Roman Empire in the fifth century. Provincial building throughout the Roman Empire reflected that of Imperial Rome, and its architecture is exactly parallel. Civic buildings included baths, amphitheaters, temples and forum, of which a typical forum building is shown here.